HUBUNGAN ANTARA DISTRESS DAN DUKUNGAN SOSIAL DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA DALAM MENYUSUN SKRIPSI - Andarini, Sekar Ratri; Fatma, Anne (TALENTA, 2013)
Delay the preparation of the thesis can be regarded as academic procrastination, which is kind of  delays  that  made  the tasks  related to  formal  academic  (Joseph  Ferrari,  1995). Students who  feel distress and perform procrastination of the  thesis work, need to get support from the people around him.   The purpose  of this study  to  determine the relationship  between  social support  to students with academic procrastination in writing his thesis.   Subjects in this study Sahid University of Surakarta student in 2005-2007 and the forces working on thesis or final project. Sampling was purposive sampling with the measuring tool of procrastination scale, scale stress and social support scale.   Based on calculations  between  social support  variables  with  the variable  academic procrastination obtained a correlation coefficient (r) 0.603, p = 0.000 (p <0,05). While distress variables with academic procrastination variable obtained correlation coefficient (r) of 0.318, p =  0.046  (p <0,05). The  results  showed  there was a significant negative relationship  between social support with academic procrastination